Mental health and wellbeing offerings in tertiary agriculturaleducation: a content analysis - Knook J; Stanley-Clarke N; Hay A; Flannery S; Rose DC; Janssen K (Taylor and Francis Group, 2026)
Purpose: Those working and living on-farm are facing wellbeing challenges. Resilience can be built via education programmes at a tertiary education level. However, it is unknown to what extent wellbeing education is integrated in the curriculum. This study reports on a content analysis of current wellbeing education at five universities that provide agricultural degrees, located in Aotearoa New Zealand, the United Kingdom, Ireland and the United States. Design/Methodology/Approach: The content analysis focuses on evaluating current wellbeing education. We use a framework developed from a comprehensive literature review on young rural people and mental health. The analysis involves examining course notes, learning materials, lecture recordings and related resources to identify key themes and content related to wellbeing. Findings: Wellbeing education is delivered at all universities in this study. Most of the education has derived from a response to managing risk, but steps are being taken to provide a more rounded offering. Key aspects to consider in the development of wellbeing education are scaffolded learning and the inclusion of external stakeholders. Practical implications: The findings offer actionable recommendations for universities to enhance their wellbeing education,strengthening support systems and promoting mental health and wellbeing among students. Theoretical implications: The study enriches existing frameworks on youth mental health by providing insights into how wellbeing is integrated into higher education curricula for agricultural students,identifying key areas of focus and opportunities for improvement. Originality/value: The study provides insight into wellbeing education in tertiary degrees in agriculture. It provides recommendations for future integration into the curriculum.